Reviewing Internal Variables on the Level of Underpricing of IPO Shares (Observation of the Company Go Public on IDX 2021-2022) - Jufri Yandes; Sapto Setyo Nugroho (Yayasan Ilomata, 2023)
This research study was held to examine internal variables that can determine the effect of stock underpricing levels when conducting an IPO (Initial Public Offering) on the IDX (Indonesia Stock Exchange) 2021-2022. Internal factors include ROE and ROA. Research is quantitative and uses secondary data, explanatory research study type, using methods by purposive sampling when determining samples. The novelty of the study can be seen from the overall data and the latest samples used by 64 issuers and the periods used, namely 2022 and 2021. The study used hypothesis testing methods, including multiple linear regression analysis through the help of Eviews (Econometric Views). The source of data used in this study is prospectus data issued by companies or issuers that go public with underwriters. The calculation results obtained partially produce ROE and ROA variables have a significant influence on the level of underpricing in IPO shares, and simultaneous results show that ROE and ROA variables together have a significant effect on the level of underpricing of IPO shares. The result of a positive value coefficient is obtained at the IPO stock underpricing level, then the ROE variable has a negative coefficient and the ROA coefficient is positive, this is interpreted by the increase in the ROE value, the stock underpricing level will decrease and apply to vice versa, and for the ROA variable that has a positive coefficient means that the more the ROA value increases, the stock underpricing level will also increase and vice versa.